Anchorage-dependent multicellular aggregate formation induces CD44 high cancer stem cell-like ATL cells in an NF-κB- and vimentin-dependent manner. Issue 1 (1st February 2015) - Miyatake, Yukiko; Sheehy, Noreen; Ikeshita, Shunji; Hall, William W.; Kasahara, Masanori
Abstract Adult T-cell leukemia/lymphoma (ATL) is an intractable T-cell malignancy accompanied by massive invasion of lymphoma cells into various tissues. We demonstrate here that ATL cells cultured on a layer of epithelial-like feeder cells form anchorage-dependent multicellular aggregates (Ad-MCAs) and that a fraction of MCA-forming ATL cells acquire CD44 high cancer stem cell-like phenotypes. ATL cells forming Ad-MCAs displayed extracellular microvesicles with enhanced expression of CD44v9 at cell synapses, augmented expression of multidrug resistance protein 1, and increased NF-κB activity. Blockade of the NF-κB pathway dramatically reduced Ad-MCA formation by ATL cells and the emergence of CD44 high ATL cells, but left a considerable number of ATL cells adhering to the feeder layer. Disruption of vimentin cytoskeleton by treatment with withaferin A, a natural steroidal lactone, suppressed not only the adhesion of ATL cells to the feeder layer but also subsequent Ad-MCA formation by ATL cells, suggesting the involvement of vimentin in anchoring ATL cells to the feeder layer. Ad-MCA formation by ATL cells on a layer of epithelial-like feeder cells may mimic critical events that occur in metastatic colonization.